Improving the Reliability of Current Collectors in Electric Vehicles; Mathematics; Vol. 13, iss. 12 - Malozyomov B. V. Boris Vitaljevich; Martyushev N. V. Nikita Vladimirovich; Demin A. Yu. Anton Yurievich; Pogrebnoy A. V. Aleksandr Vladimirovich; Efremenkov (Ephremenkov) E. A. Egor Alekseevich; Valuev D. V. Denis Viktorovich; Boltrushevich A. E. Aleksandr Evgenjevich (2025, 2025)
Title screen